Decomposition of Mediterranean Dietary Pattern on Successful Aging, Among Older Adults: A Combined Analysis of Two Epidemiological Studies. (October 2019) - Foscolou, Alexandra; Koloverou, Efi; Matalas, Antonia-Leda; Tyrovolas, Stefanos; Chrysohoou, Christina; Sidossis, Labros; Rallidis, Loukianos; Panagiotakos, Demosthenes B.
Objective: To investigate the association of Mediterranean food group consumption with successful aging (SA), among people more than 50 years old.Method: Dietary habits, as well as several bio-clinical characteristics of the Greek participants enrolled in the ATTICA ( n = 1, 128 men and women from Athens metropolitan area) and the MEDIS ( n = 2, 221 men and women from selected Greek islands) cohort studies were investigated in relation to SA; SA was measured using a validated 10-scale index.Results: Multivariate discriminant food group analysis revealed that legumes consumption, followed by vegetables, cereals, and poultry were associated with higher levels of SA index (explained variability: 7.9%), mainly among islanders, but not among mainland participants. Further analysis revealed that alcohol consumption was positively associated with SA for mainlanders (ATTICA study) but inversely for islanders (MEDIS study; all p 's < .05).Conclusion: The differential and hierarchical effect of various foods on SA and the diet-environmental interaction revealed in the present work may help health professionals to better understand the role of diet on SA, and to prioritize the nutritional needs of older people for better quality of life.